A global pandemic in the time of viral memes: COVID-19 vaccine misinformation and disinformation on TikTok. Issue 8 (3rd August 2021) - Basch, Corey H.; Meleo-Erwin, Zoe; Fera, Joseph; Jaime, Christie; Basch, Charles E.
ABSTRACT: Misinformation and disinformation regarding COVID-19 and vaccination against it may be contributing to vaccine hesitancy. Social media outlets have reportedly made efforts to limit false information yet untruths related to COVID-19 persist online. The purpose of this study was to describe the content on COVID-19 vaccination on TikTok, an emerging social media platform. One-hundred trending videos were identified from the hashtag #covidvaccine and were coded for content. Collectively, these videos garnered over 35 million views. The coding category with the highest number of videos was "Discouraged a Vaccine" (n = 38), followed by "Encouraged a Vaccine" (n = 36). While only 36 videos encouraged a vaccine, these videos garnered over 50% of the total cumulative views and just under 50% of the total likes; the 38 videos that discouraged a vaccine garnered 39.6% of the total cumulative views, 44.3% of likes, and 47.4% of comments. Of the 38 videos discouraging the vaccine, 25 (65.79%) showed a parody of an adverse reaction and, collectively, received 71.07% of the total views among videos in this category. Twenty-two of these 38 videos (57.89%) falsely conveyed that a vaccine was available, as they were not at the time of the study. Anti-vaccination messaging may undermine efforts to ensure widespread uptake of the various COVID-19 vaccines, particularly for young people who are more likely than other age cohorts to use TikTok.